Close Family Economic System: Pilah-Olah Sampah Rumah Tangga Bernilai Ekonomis di Wilayah RW 02 Kelurahan Karanganyar Gunung Kecamatan Candisari Kota Semarang: Close Family Economic System: Sorting and Processing Household Waste with Economic Value in RW 02 Area, Karanganyar Gunung Village, Candisari District, Semarang City - Sijabat, Rauly; Suwarti, Tarcisia Sri; Widiyanto, Muh. Wahyu; Zaidah, Nuning (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The problem of waste is not only faced by the country, but Semarang City, especially Karanganyar Gunung Village, also faces the same problem. Data shows that waste generated from household activities contributes the most to national and regional waste sources. Therefore, it is necessary to involve households in aspects of waste management. The Close Family Economic System is an approach to sorting and processing waste that generates economic value, which households can achieve. This system offers activities to sort organic and inorganic waste, allowing it to have economic value. Inorganic waste is sorted according to its characteristics to be then sold to collectors. At the same time, organic waste is processed simply into aromatherapy candles and ecoenzymes. The proceeds from the sale of waste are then managed or returned to residents to drive household economic activities.